Mithun (Bos Frontalis): A Forest-Based Food Animal Of The Eastern Hima layas - Kumar, Harshit; Choudhary, Jagdish; Chotso, Kuluve; Moon Mech, Moon; Sunitibala Devi, L; Stephen Hanah, Sapunii; Kumar Chamuah, Jayanta; Patil Shivanagowda, Girish (Journal of Meat Science, 2026)
Mithun (Bos frontalis) is a domesticated bovine native to the Eastern Himalayas, traditionally managed under forest-based systems and primarily utilized for meat by indigenous communities. Despite its cultural and nutritional importance, Mithun remains underrepresented in formal meat production research and development programs. This review critically evaluates existing literature with emphasis on meat production potential, carcass characteristics, meat quality attributes and biological determinants influencing growth and meat yield. Evidence from studies encompassing nutrition, growth physiology, genetics, reproduction and health management indicates that Mithun exhibits favorable meat composition, efficient utilization of fibrous forest biomass and inherent adaptability to low-input production environments. Available data also suggest the presence of genetic traits associated with disease tolerance and environmental resilience, which may indirectly influence meat productivity. Advances in reproductive biotechnologies, genomic characterization and microbiome research offer new opportunities for genetic improvement and conservation of meat-related traits. However, habitat degradation, genetic erosion, limited performance recording and lack of organized slaughter and processing infrastructure constrain its integration into structured meat value chains. The review highlights the need for targeted research on growth performance, carcass evaluation and meat quality parameters, coupled with conservation-oriented breeding and value-chain development. Positioning Mithun as a niche forest-based meat animal may support sustainable meat production and livelihood enhancement in the Eastern Himalayan region.